Pengaruh Leaflet Covid-19 Terhadap Ibu Dan Bayi Pada Masa Pandemi Di Praktik Mandiri Bidan - Deni Maryani; Dara Himalaya (Oksitosin : Jurnal Ilmiah Kebidanan, 2021)
Early 2020, the Corona virus (Covid-19) was officially designated by the WHO as a dangerous infectious disease that can be transmitted to humans. During the pandemic situation, the group that is vulnerable to contracting Covid-19 is the midwife, whose main task is maternal and child health services at the basic level. Midwives must understand how the protocol for maternal and child health services is to avoid the transmission of Covid-19. The purpose of this study was to analyze the effect of the Covid-19 leaflet protocol on maternal and infant care, the research method used was quasi-experimental, with one group pre and post test. The population in the study was midwives who opened independent practice during the Covid-19 pandemic in Bengkulu City, the sampling technique was random sampling, which returned 35 samples. Data analysis with chi square method. The results of the statistical test showed that the level of knowledge of respondents after being given the Covid-19 protocol leaflet for maternal and infant services, there was an increase in the good category from 71.43% to 94.29%. The category was originally 57.1% to 5.71%, and knowledge was low from 20.0% to 0.0%. There is a difference in the level of knowledge after giving the intervention and before giving the intervention using leaflet media and there is no difference in attitude between before the intervention and the intervention after using the leaflet. Keywords: Leaflet, Maternal Neonatal,Covid-19 ABSTRAK Awal tahun 2020 Coronavirus (Covid-19) resmi ditetapkan oleh WHO sebagai penyakit infeksi berbahaya yang dapat menular ke manusia. Saat situasi pandemi kelompok yang rentan untuk tertular Covid-19 adalah bidan, dimana tugas utamanya adalah melayani kesehatan ibu dan anak ditingkat pelayanan dasar. Bidan harus memahami bagaimana protokol pelayanan kesehatan ibu dan anak, agar terhindar dari penularan Covid-19. Tujuan penelitian ini adalah menganalisis pengaruh leaflet protokol Covid-19 terhadap pelayanan ibu dan bayi, metode penelitian yang digunakan adalah quasi experiment, dengan satu grup pre dan post test. Populasi dalam penelitian adalah bidan yang membuka praktik mandiri selama pandemi Covid-19 di Kota Bengkulu, teknik pengambilan sampel dengan random sampling yaitu berjumlah 35 sampel. Analisis data dengan metode chi square. Hasil uji statistik didapatkan tingkat pengetahuan responden setelah diberikan leaflet protokol Covid-19 pelayanan ibu dan bayi, terjadi peningkatan untuk kategori baik dari 71.43% menjadi 94.29%. Kategori sedang yang awalnya 57.1% menjadi 5.71%, dan pengetahuan rendah dari 20.0% menjadi 0.0%. Terdapat perbedaan tingkat pengetahuan bidan setelah pemberian intervensi dan sebelum pemberian intervensi dengan menggunakan media leaflet dan tidak terdapat perbedaan sikap antara sebelum intervensi dan setelah intervensi dengan menggunakan leaflet. Kata Kunci: Leaflet, Maternal Neonatal, Covid-19